Which Gating System Can Prevent Addiction to Online Games?. (1st February 2023) - Matheus, Flobert; Jayadi, Riyanto
Abstract : The online game industry has increased time by time. Because of that, many addiction cases emerge in humans. In addition, some factors could make people addicted and mitigate or prevent the addiction. However, this addiction has already created some problems, such as skipping school (mild cases) to murder cases (huge cases). A gating system is a system that could prevent players from experiencing some content in the game after a specific limit has been reached. This study is aimed at identifying which gating systems in online games could make players more addicted and which systems are the most appropriate to mitigate or prevent addiction to online games. The study is done with a survey from online game communities with 458 samples in Indonesia. The result of the study shows that resource is the factor that affects addiction, and the stamina gating system is the one that affects resource as mitigation of addiction. This research shows that the stamina gating system will affect how players manage their resources in real life so that they will not be addicted to the game.